ANALISIS OPEN INNOVATION DITINJAU DARI PERSPEKTIF RESOURCE BASED VIEW (RBV) THEORY - Yulianti, Prima; Masruri, Masruri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.04.TAHUN.2024DO - 10.24843/EEB.2024.v13.i04.p01, 2024)
Companies adopt open innovation to improve company performance. The level of openness of MSMEs, whose resources and capacities are different from those of large companies, is still underrepresented and receives little attention. Resource-Based View (RBV) Theory states that unique and rare resources become a competitive advantage for companies. This research aims to analyze open innovation, based on human capital, knowledge sharing, social media and its impact on business performance from a Resource-Based View Theory perspective. The sample was 162 respondents from MSMEs in Padang City. The sample determination technique is purposive sampling. The method used is a quantitative method, then processed and analyzed using the structural equation modeling (SEM) data analysis technique model with smartPLS. The findings in this research are that there is a positive and significant influence of human capital and social media on open innovation, while knowledge sharing does not have a positive and significant influence on open innovation. Apart from that, open innovation has succeeded in mediating the relationship between human capital and business performance. However, it was not successful in mediating the relationship between knowledge sharing and social media on business performance. It is hoped that this research can be used by business actors in determining policies to innovate and improve the performance of MSMEs in the future